PENINGKATAN KEMAMPUAN MENULIS CERPEN DENGAN MENGGUNAKAN TEKNIK PARAFRASE PUISI SISWA KELAS X1 SMA PERTIWI 1 PADANG - Wulandari, Yosi; Rahmi, Ega Aulia (Jurnal Varidika: Varia Pendidikan, 2012)
The purpose of the research was to explain and analyze the short story writing skills improvement grades X1 SMA Pertiwi 1 Padang in terms of characterization, plot, and setting. This type of research is a classroom action research that uses four stages in each cycle, including planning, implementation, observation, and reflection. The research was conducted in two cycles. The data was collected through two main instruments, namely test and nontes. The test is used to collect data capability to write short stories, while the form of sheets nontes observation, field notes, and questionnaires were used to collect the data in the application of learning techniques paraphrasing poetry writing short stories. Analyzing data in accordance with the descriptive-analytical application of the concept of action research. Results of this study showed that the results of the students wrote short stories on pre-cycle obtain an average value of 58.89, cycle 1 with an average value of 77.04, and in cycle 2 the average score was 91.11.. The results showed an increase of pre-cycle students write short stories until the cycle 2.